2021
DOI: 10.3390/su13084418
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Deployment and COVID-19 Measures for Sustainable Development

Abstract: The main goal of this study is to evaluate the impact of restrictive measures introduced in connection with COVID-19 on consumption in renewable energy markets. The study will be based on the hypothesis that similar changes in human behavior can be expected in the future with the further spread of COVID-19 and/or the introduction of additional quarantine measures around the world. The analysis also yielded additional results. The strongest reductions in energy generation occurred in countries with a high perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The unit elasticity theory, which tends to measure the change in economic growth concerning change in energy consumption, has gained much prominence after the oil crisis of 1973, also known as the C74 crisis, and its impact on the OECD countries during this period. The unit elasticity for energy usage after that period has been recorded as less than 1%, which signifies that 1% economic growth requires a less than 1% increase in energy usage as far as OECD countries were concerned [17,18]. However, no one can deny the critical role energy consumption plays in generating GDP growth, mainly via industrial development.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The unit elasticity theory, which tends to measure the change in economic growth concerning change in energy consumption, has gained much prominence after the oil crisis of 1973, also known as the C74 crisis, and its impact on the OECD countries during this period. The unit elasticity for energy usage after that period has been recorded as less than 1%, which signifies that 1% economic growth requires a less than 1% increase in energy usage as far as OECD countries were concerned [17,18]. However, no one can deny the critical role energy consumption plays in generating GDP growth, mainly via industrial development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, a major obstacle to renewable energy sources seems to be political barriers, such as obstructive policies based upon self-interest, problems related to coordination of activities, and problems related to geopolitical issues. These problems are further compounded by the limited research in the area [18,25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, this study referenced and categorized relevant domestic and international results (also covering previous years and months of the lockdown period) to summarize the characteristics of various air pollutants in several regions and to obtain a more in-depth understanding of air quality improvement and PM 2.5 compositions in Xi'an during this event. The lockdown caused by the COVID-19 pandemic provided an opportunity to perform a natural experiment for evaluating air quality responses to drastic emission reduction, and it is helpful to formulating more targeted policies in this heavily polluted area and sustainable development [33,42,43]. In line with this, future awareness campaigns should focus more on a multidisciplinary area in practitioners from all walks of life towards Penta Helix Collaboration [44][45][46] in the post-COVID-19 world [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…In studies dealing with territories for the European continent [207], it was concluded that renewable energy development policies improve the social factors studied (government policy, general public awareness, the market, lobbying activity) [207]. Russia was studied in [208], and the United Kingdom and Germany in [209] together with the USA and Brazil. On the Asian continent, Iran, China and Cambodia were investigated by [210,211] and [212], respectively.…”
Section: Discussionmentioning
confidence: 99%